D-amino acid enhanced the sensitivity of avian pathogenic Escherichia coli to tetracycline and amikacin - Wu, Jing; Yang, Bin; Jiang, Wei; Yin, Huifang; Han, Xiangan; Zhang, Lili (Frontiers in Veterinary Science, 2025)
Avian pathogenic Escherichia coli (APEC) biofilm formation has led to increased antibiotic resistance, presenting a significant challenge for the prevention and control of the disease. While certain D-amino acids (D-AAs) have been shown to inhibit the formation of various bacterial biofilms, role in APEC biofilms remains unexplored. This study investigates the effects of 19 different D-AAs on clinically isolated APEC biofilm. The results showed that D-tyrosine (D-Tyr), D-leucine (D-Leu), D-tryptophan (D-Trp), and D-methionine (D-Met) can reduce APEC formation by over 50% at a concentration of 5 mM. Subsequently, four D-AAs were selected for combination treatment with antibiotics (ceftazidime, amikacin, tetracycline, and ciprofloxacin). The findings reveal that D-Tyr enhance the sensitivity of APEC to amikacin and tetracycline, while D-Met increases the sensitivity of APEC to amikacin. The mechanisms by which D-Tyr and D-Met enhance antibiotic sensitivity were further investigated. Following treatment with D-Tyr and D-Met, scanning electron microscope (SEM) observations indicated a reduction in the number of bacteria on the surface of the cell crawl, but the shape and structure of the cells remain unchanged. Notably, the surface hydrophobicity was decreased by 33.86% and 56%, and the output of extracellular polysaccharide was decreased by 46.63% and 57.69%, respectively. Additionally, genes related to biofilm synthesis (pgaA, pgaC, and luxS) were down-regulated (p < 0.05), whereas porin protein-encoding genes (ompC and ompF) were up-regulated (p < 0.05), which inhibited formation of biofilm and enhanced the sensitivity of APEC to amikacin and tetracycline and by decreasing the hydrophobicity and extracellular polysaccharide content on cell surface and up-regulated porin genes and down-regulating the genes related to biofilm formation. According to the different D-AAs involved in this study, it can provide new ideas for the treatment of APEC.